The Residences of Turkic Khagans in Chach: Jabghukat and Khatunkat - Khatamova Мунира (Turkic Studies Journal, 2021)
In this article the author states opinions concerning occurrence and function of one of residences Turkic khaghans – Jabγukat (site Ak ata), located in Chach. In particular, it has arisen in the end VI of century in connection with Turkic khaghanate, and carried out functions both military, and political residence. At the same time near it there is a city Xatunkat (site Tugaytepe), that testifies to a strategic role Chach and reflection here of traditions statehood ancient Turks. These «city Khatun» arose in different territories, where widespread Turkic ethnic groups. The author of the article considers some of them came to the conclusion that the presence of «Khatun city» is one of the characteristics inherent in the urban planning of the ancient Turks.